Lessons from the History of Internet Studies - Allen Matthew (Cultural Science)
A Keynote Presentation given at the Open Literacy Digital Games, Social Responsibility and Social Innovation Symposium in celebration of the 20-year anniversary of the founding of Internet Studies at Curtin University. Matthew is Australia’s first Professor of Internet Studies, having established the world-leading Internet Studies department at Curtin University where he worked from 1993 to 2012.